Perforated wellbore stability - Samsuri, Ariffin (1991)
This paper presents the results of a study into the mechanical stability of perforated wellbore and the factors which affect it. Physical models of the main factors associated with perforated wellbore were generated and exposed to various load regimes and conclusions were drawn with respect to optimising the stability and therefore the productivity of the perforated well. The results show that the failure depends on the pressure differential between wellbore and formation, the perforation length, shot density, phasing angle and pattern.